Analysis of Legal Reasoning of Judge's Ruling Number 0124/PDT.P/2019/PA.SAL Concerning Pre-Marriage Pregnancy Marriage from An Islamic Legal Perspective - Muhammad Johansyah Maulana; M. Junaidi (Universitas Muhammadiyah Surakarta, 2023)
Marriage age is the most crucial element in the household. The age limit for Indonesian citizens is principally intended so that anyone who marries has a mature mind, a mature soul and sufficient physical strength, so that the potential for marital breakdown which leads to divorce can be avoided because they have a mature understanding and awareness regarding the purpose of marriage. which focuses on aspects of inner and outer happiness. This research uses a type of normative legal research by examining regulatory aspects regarding the concept of implementing legal protection for marriage in Decision 0124/Pdt.p/2019/PA.Sal and Law Number 16 of 2019. The judge's reasons for granting marriage dispensation by the applicant are by considering the goodness or the benefit of the people, the benefit of the child being conceived by the bride who is currently 4 months pregnant. Granting the reason for marriage dispensation must be prioritized because it is feared that it will cause greater damage. These reasons are considered by the judge in granting the request for marriage dispensation in the Compilation of Islamic Law in Indonesia which is set out in Keppers No. 1 of 1991 and Decree of the Minister of Religion No. 154/1991 stipulates that a woman who becomes pregnant outside of marriage can only be married to the man who impregnated the woman. This kind of marriage can be carried out directly without waiting for the birth of the baby the woman is carrying and there is no need for remarriage (tajdidun nikah).